Track2KBA: An R package for identifying important sites for biodiversity from tracking data. Issue 12 (24th September 2021) - Beal, Martin; Oppel, Steffen; Handley, Jonathan; Pearmain, Elizabeth J.; Morera‐Pujol, Virginia; Carneiro, Ana P. B.; Davies, Tammy E.; Phillips, Richard A.; Taylor, Philip R.; Miller, Mark G. R.; Franco, Aldina M. A.; Catry, Inês; et al.
Abstract: Identifying important sites for biodiversity is vital for conservation and management. However, there is a lack of accessible, easily applied tools that enable practitioners to delineate important sites for highly mobile species using established criteria. We introduce the R package 'track2KBA', a tool to identify important sites at the population level using tracking data from individual animals based on three key steps: (a) identifying individual core areas, (b) assessing population‐level representativeness of the sample and (c) quantifying spatial overlap among individuals and scaling up to the population. We describe package functionality and exemplify its application using tracking data from three taxa in contrasting environments: a seal, a marine turtle and a migratory land bird. This tool facilitates the delineation of sites of ecological relevance for diverse taxa and provides output useful for assessing their importance to a population or species, as in the Key Biodiversity Area (KBA) Standard. As such, 'track2KBA' can contribute directly to conservation planning at global and regional levels. Resumo: A identificação de áreas importantes para a biodiversidade é essencial para a sua conservação. No entanto, são escassas as ferramentas acessíveis e de fácil aplicação que permitam o delineamento de áreas importantes para espécies altamente móveis usando critérios estabelecidos. Neste estudo, apresentamos o pacote de R 'track2KBA', uma ferramenta para identificar áreas importantes ao nível populacional usando dados de seguimento de animais com base em três passos principais: (1) identificação de áreas vitais dos indivíduos, (2) avaliação da representatividade da amostra ao nível da população, (3) e quantificação da sobreposição espacial entre indivíduos e extrapolação para a populacão. Descrevemos a funcionalidade do pacote e exemplificamos a sua aplicação usando dados de seguimento de três éspecies ‐ lobo‐marinho, tartaruga marinha e uma ave terrestre migradora‐ em ambientes contrastantes. Esta ferramenta facilita o delineamento de áreas com relevância ecológica para diversos taxa e fornece resultados importantes para avaliar a sua importância para uma população ou espécie, utilizando por exemplo o Key Biodiversity Area (KBA) Standard. Como tal, o 'track2KBA' pode contribuir directamente para o planeamento da conservação a nível global e regional.